An ANALYSIS OF THE SUBTITLE OF SIMILE AND PERSONIFICATION IN ANNA KARENINA (2012) MOVIE - Kesia Ariani Citra; Sulistini Dwi Putranti; Neneng Sri Wahyuni (LINGUA : JURNAL ILMIAH, 2020)
The focus of this research is to analyze the subtitle of 2 types of figurative languages; personification and simile, taken from the Anna Karenina movie directed by Joe Wright. This research aims to reveal the types of subtitle strategies applied to translate personification and simile found in the movie. The researcher uses qualitative method and document analysis to explain and describe the data. To analyze personification and simile, the researcher uses the theory of personification and simile proposed by Perrine (1997). Meanwhile, the researcher uses the theory of subtitle strategies proposed by Gottlieb (1992) to analyze the subtitle strategies. The researcher finds that there are 2 data classified as personification and 5 data classified as simile. However, there are 3 of 10 strategies applied to translate personification and simile, those are transfer, decimation and deletion. The result of this research indicates that the most used of the subtitle strategy is transfer. By using transfer strategy, all of the messages in the subtitles are delivered well because there is one on one equivalent in SL and TL.